Monetary Policy Response to Exchange Rates: An Empirical Investigation - Yagmur, Mete Han (International Journal of Economics and Financial Issues, 2016)
Notwithstanding exchange rate stability concerns in practice, exchange rate arguments are often omitted from monetary policy analysis and simple interest rate rules do not comprise exchange rate arguments even in small open economy set-ups. In order to identify the role of exchange rates in monetary policy conduct, we append them into a Taylor type of rule and examine their effect on policy interest rates in the US, UK, Canada, and Norway by utilizing General Method of Moments (GMM). The results suggest that for big and relatively closed economies, such as the US, exchange rate movements do not lead to significant response in policy interest rates. Nevertheless, for small open economies, both exchange rate variability and exchange rate levels are significant in monetary policy conduct. Keywords: Exchange rate stability; Monetary policy; GMM method JEL Classifications: E43; E52; E58; F31